The effect of a 5-week therapeutic massage on erector spinae and upper trapezius muscle stiffness as determined by shear-wave elastography: a randomized controlled trial - Jelen, Amadej; Javornik, Erina; Meh, Sara Gloria; Kozinc, Žiga (Frontiers in Sports and Active Living, 2024)
Massage is an effective treatment for reducing pain, swelling, stiffness, and improving muscle mobility. Although self-reported benefits on muscle stiffness and pain are well-known, studies measuring muscle stiffness objectively are scarce. A randomized controlled trial involving thirty recreationally active young women (22.3 ± 0.4 years) was conducted. The participants were randomly assigned to either the control group or the intervention group which received a series of five 30-min whole back therapeutic massage sessions over five weeks. Shear wave elastography was used to assess muscle stiffness (erector spinae (ESp) and upper trapezius (UT) muscles) before and after the intervention and at 3-week follow-up. For ESp, there was no statistically significant time × group interaction (F = 2.908; p = 0.063). However, there was a statistically significant and large time × group interaction for UT (F = 13.533; p = 0.006; η2 = 0.19). Post-hoc testing for time indicated that the shear modulus in the intervention group was reduced at follow-up (p = 0.005; d = 1.02), while the difference between baseline and post-intervention measurements were not statistically significant (p = 0.053; d = 0.75). In conclusion, massage significantly reduced proximal UT stiffness both 3 days and 3 weeks after the intervention. However, it had no significant effect on the distal part of UT or the ESp muscle.